Persekutuan Kristen PERSEKUTUAN KRISTEN DAN TANTANGANNYA DI ERA SOCIETY 5.0: Persekutuan Dalam Perjanjian Lama - Bani, Yulianus; Karbui, Titus; Lontaan, Jemmy; Tuaty, Mathcostantein Ericktus Illu; Wau, Robah; Zai, Kalvinus (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2024)
Fellowship is a very fundamental thing in Christianity. At the beginning, God created humans with one goal, namely to have fellowship with them. The fellowship between God and man was broken due to sin, but in Christ it has been restored. Therefore, Christian fellowship concerns three aspects, namely with God, fellow believers and fellow humans. However, over time, Christian fellowship has become a serious problem and must be given special attention. Christians still have the problem of fellowship with God, believers and unbelievers. One of the factors influencing Christian fellowship is the development of information technology or what is better known as the era of society 5.0. Researchers use qualitative methods that utilize books, articles that are related to this paper. The author also carried out investigations and analyzes of every source related to this research. This research places emphasis on Christian fellowship as the responsibility of believers throughout the era. The research results found that many Christians ignore fellowship with God, believers and non-believers. This research emphasizes that Christian fellowship must be the focus of churches, schools, STTs and Christian institutions. Christian fellowship should be a basic need for every Christian throughout the ages.